If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4x+8=2x(2x+4)
We move all terms to the left:
4x+8-(2x(2x+4))=0
We calculate terms in parentheses: -(2x(2x+4)), so:We get rid of parentheses
2x(2x+4)
We multiply parentheses
4x^2+8x
Back to the equation:
-(4x^2+8x)
-4x^2+4x-8x+8=0
We add all the numbers together, and all the variables
-4x^2-4x+8=0
a = -4; b = -4; c = +8;
Δ = b2-4ac
Δ = -42-4·(-4)·8
Δ = 144
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$$\sqrt{\Delta}=\sqrt{144}=12$$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-4)-12}{2*-4}=\frac{-8}{-8} =1 $$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-4)+12}{2*-4}=\frac{16}{-8} =-2 $
| -13.1=2.2x+4.5 | | 6+4(3x-6)=5-3(2x+1) | | 50+2x=80 | | 36=13n−4n36=13n−4n. | | -5=3m- | | 3x-1/2=5x+2/3+1 | | -5=2(10b-2)=31 | | 4x+8=2x(2x-4) | | 4x+8=2x(2x-8) | | -6(4x-5)+5(5x-3)-2=6-7 | | 180-x=3×(90-x)+30 | | 2/h-1/3h+11=8 | | 6x-1/6=9 | | x-16x+3x=180 | | 3/5=2x-6/3+x/5 | | x+30/8=1/4x | | 13z-8z=20 | | -131=22x+45 | | -6x-8=3x+5 | | 4x+1+47=180 | | 3w=-27+12w | | 19-3(a-6)-18=66 | | 6x(-12/3)+4=18/x | | 6(x-3)^2=0 | | (-3-4i)-(-3+5i)=0 | | 4x+3=2x(2x+3) | | Y=3/2x-13/2 | | -30=-8x-14 | | x^2-16x-3x=180 | | 4K-4+3k=5k+16 | | 8-4a=12 | | x^2-1=-x^2+3 |